Effect of double-induced on whey protein isolate nanoparticle formation and stabilized food-grade Pickering emulsions: Stability and gastrointestinal digestion - Shenghua He; Yonghui Wang; Guanghui Li; Xueli Gao; Zhiyan Chen; Weiyun Guo; Jihong Huang (Food Chemistry: X)
The effects of non-heat-induced and double-induced(heat-induced and Na+-induced) whey protein isolate nanoparticles (WPINs) at concentrations of C = 1 %, 2 %, and 5 % as well as oil fractions (φ = 0.1, 0.4, and 0.7) on the properties of food-grade Pickering emulsions (PEs) were systematically investigated. At a Na+ concentrations of 300 mM, the particle size of double-induced WPINs (290 μm) is significantly larger (P < 0.05) than that of non-heat-induced WPINs (210 μm). PEs stabilized by double-induced WPINs exhibited a significantly small particle size (P < 0.05) compared to those stabilized by non-heat-induced WPINs under identical oil fraction and WPIN concentration conditions. Additionally, PEs with φ = 0.7 stabilized by double-induced WPINs enhanced storage and thermal stability. However, both types of PEs exhibited freeze-thaw instability. PEs stabilized by double-induced WPINs showed a slower release rate of free fatty acid during gastrointestinal digestion. These findings highlight the promising application potential of WPINs in food-grade Pickering emulsion.